2014
DOI: 10.1212/wnl.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease is associated with dementia independent of cerebral small-vessel disease

Abstract: CKD is independently related to the risk of all-cause dementia in patients with vascular risk factors. Our results reinforce the hypothesis that CKD exerts deleterious effects on dementia incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 29 publications
8
88
0
6
Order By: Relevance
“…Further, the association of global CI with WMH and cerebral atrophy was independent of CVD history and CVD risk factors for the whole CKD group. These findings might be supported by previous studies indicating that CKD, per se, contributes to cognitive decline [36], independent of ischemic cerebral lesions [35], and that HD is associated with CI, independent of CVD risk factors, SVI, and brain atrophy [37]. Indeed, white matter lesions, which were shown to be a strong predictor of general CI in our study, could be present not only in stroke but also in multiple sclerosis [38], pyridoxine deficiency, and cerebral metabolic disturbances in CKD patients [18].…”
Section: Discussionsupporting
confidence: 83%
“…Further, the association of global CI with WMH and cerebral atrophy was independent of CVD history and CVD risk factors for the whole CKD group. These findings might be supported by previous studies indicating that CKD, per se, contributes to cognitive decline [36], independent of ischemic cerebral lesions [35], and that HD is associated with CI, independent of CVD risk factors, SVI, and brain atrophy [37]. Indeed, white matter lesions, which were shown to be a strong predictor of general CI in our study, could be present not only in stroke but also in multiple sclerosis [38], pyridoxine deficiency, and cerebral metabolic disturbances in CKD patients [18].…”
Section: Discussionsupporting
confidence: 83%
“…7 A recent longitudinal study in 600 patients with vascular risk factors found that CKD was related to all-cause dementia independent from vascular risk factors and baseline cerebral small vessel disease. 54 These findings suggest that vascular damage is not the only possible explanation of the association.…”
Section: Continuedmentioning
confidence: 96%
“…59 Alteration in memory function that is suggestive of an Alzheimertype dementia can occur in CKD, but the cognitive changes in this condition typically indicate a combination of neurodegenerative dementia, such as Alzheimer disease and vascular dementia. 60 Even in the absence of overt neurological changes, cognitive impairment can be detected in patients with CKD through the use of psychometric tests. 61 Such tests include the Kidney Disease Quality of Life, 62 MiniMental Status Examination, 63 the Modified Mini-Mental State Exam, 64 the 6-Item Screener, 65 St Louis University Mental Test, 66 and the Montreal Cognitive Assessment.…”
Section: Cognitive Testing In Patients With Ckdmentioning
confidence: 99%